2014
DOI: 10.1136/bcr-2014-206271
|View full text |Cite
|
Sign up to set email alerts
|

Significant biventricular obstruction in non-syndromic hypertrophic cardiomyopathy

Abstract: DESCRIPTIONAlthough hypertrophic cardiomyopathy (HCM) is classically considered a disease of the left ventricle (LV), we present a rare case of biventricular HCM presenting in middle age.A 57-year-old man without a family history of HCM and sudden death presented with presyncope and New York Heart Association (NYHA) class II breathlessness. Clinical examination was normal except for ejection systolic murmur. ECG showed biventricular hypertrophy with deep T-wave inversions. Echocardiography demonstrated pronoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The previous works indicated that biventricular resection was ineffective and associated with a high risk of death. However, biventricular resection was successfully performed in a 54-year-old woman (LVIPG = 150 mmHG, RVIPG = 130 mmHG) [ 25 ] and a 57-year-old man (LVIPG = 109 mmHg, RVIPG = 138 mmHg) [ 26 ] with lasting outcomes. Quintana, Johnson [ 19 ] recently indicated that relief of BVOTO could be achieved with low mortality and good long-term outcomes via biventricular resection in children and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…The previous works indicated that biventricular resection was ineffective and associated with a high risk of death. However, biventricular resection was successfully performed in a 54-year-old woman (LVIPG = 150 mmHG, RVIPG = 130 mmHG) [ 25 ] and a 57-year-old man (LVIPG = 109 mmHg, RVIPG = 138 mmHg) [ 26 ] with lasting outcomes. Quintana, Johnson [ 19 ] recently indicated that relief of BVOTO could be achieved with low mortality and good long-term outcomes via biventricular resection in children and young adults.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we describe the very rare condition of biventricular hypertrophy with right ventricle obstruction. This condition is extremely uncommon and results from excessive muscular hypertrophy [4] . Analysis of speckle tracking of the myocardium showed typical normal longitudinal strain values at the apex of the left ventricle, and reduced strain at all basal segments, suggesting amyloidosis.…”
Section: Discussionmentioning
confidence: 99%